Evaluation of Bacillus-Associated Polyethylene Terephthalate (PET) surfaces for biodegradation - Khalida Khalil,; Aina Liyana Mohamad Desa,; Nurul Aisyah Ruslan,; Nazlina Haiza Mohd Yasin,; Farah Hannan Anuar,; Wan Syaidatul Aqma, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The escalating threat of polyethylene terephthalate (PET) microplastic pollution necessitates an urgent environmentally friendly approach. This study explores the potential of local bacterial isolates to biodegrade PET microplastics. Bacteria isolated from the surface of PET plastic bottles taken from Dengkil Inert Waste Landfill were screened for esterase activity and biofilm formation. PET degradation was assessed through mass weight reduction, scanning electron microscope (SEM) analysis for morphological changes, and Fourier-transform infrared spectroscopy (FT-IR) for chemical structure alterations. Two of the five selected isolates were positive for producing esterase and biofilm ability as well as biodegrade PET leading to a 2.04% - 2.08% degradation (20 days incubation). FT-IR indicated changes in PET chemical structure, particularly in C-H, C=O, and C-O bonds, while SEM revealed morphological changes such as cracks and holes on the PET surface. Identification through 16S rRNA sequencing indicated bacterial isolates are Bacillus paramycoides DIWL 1, Bacillus cereus DIWL 2, Bacillus safensis DIWL 3, Bacillus luciferensis DIWL 4, and Bacillus cereus DIWL 5. The results of this study can be used for further research on the potential of local isolates in the decomposition of PET microplastics which in turn can be used to develop a sustainable and cost-effective microplastic treatment (PET) technology.